Keragaan Pertumbuhan dan Hasil Enam Belas Genotipe Tomat (Solanum lycopersicum L.) di Dataran Rendah - Pardosi, Santi K.; Ruistikawati, Rustikawati; Suryati, Dotti (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2016)
Tomato is a high nutritional value fruit vegetables. Genetic variation is valuable plant breeding material which can be measured in terms of yield potential. This study aimed to compare the growth and yield components of 16 tomato genotypes in the lowlands. The experiment was conducted in Medan Baru Experimental Station of, Faculty of Agriculture, University of Bengkulu, with the elevation of 10 m above sea level. This was performed from September 2013 to January 2014. The experiment was set in a completely randomized design with a single factor of 16 tomato genotypes with 3 replications acounting to 48 experimental units, each of which consisted of 2 plants. The sixteen genotypes tested were Mirah, Berlian, CIN 06, SU, Kudamati 3, Lombok 3, Lombok 4, Makassar, Aceh 3, Aceh 5, Ranti Situbondo, Ranti, Situbondo Gelombang, Situbondo, Kemir, Meranti 2, Gondol Lonjong. There were significant differences in plant height, stem diameter, number of leaves, stomatal density, flowering age, harvest age, fruit diameter, fruit sweetness, fruit hardness, total fruit weight, fresh weight, and dry weight. Based on total fruit weight. The genotypes potentially cultivated in the lowlands are Ranti, Situbondo Gelombang, Kudamati 3, Situbondo, and Makassar.